(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Relevance to ethnopharmacology: Licorice, one of the primogenital and greatest well-known herbal remedies, was been used for cardiovascular diseases, antiviral, antibacterial and has ethnopharmacological significance. Multiple investigations have demonstrated that the atherosclerotic plaque contains bacterial and viral microorganisms. Pathogens can replicate in cells like macrophages or remain dormant in order to cause a chronic inflammatory environment. According to recent research, supplementing hypercholesterolemic patients with licorice extracts prevented the onset of atherosclerosis (AS). Numerous studies have demonstrated that the primary active ingredients in licorice, licorice flavonoids, have a wide range of effects in term of pharmacology, including control over lipid metabolism, anti-inflammation, and antioxidation. Licorice's primary anti-AS components are still a mystery. Aim of the study: This study aims look into the method underlying that underlie the active ingredients in licorice's anti-atherosclerotic effects. Materials and methods: In order to determine the active components, potential targets, and molecular mechanisms of licorice associated with the treatment of AS, a network pharmacology approach including oral bioavailability (OB) prediction, protein-protein interaction (PPI) network construction and analysis, and Gene Ontology term and Genomes (KEGG) pathway analyses was used. The interactions between the active compounds and the underlying targets were examined using molecular docking analysis. Results: Inclusive systems method successfully recognized 125 bioactive components from licorice as well as 39 potential targets for this medicinal herb. A number of diseases affecting the digestive organization, and respiratory organization are all closely linked to these 91 targets. To clarify the mechanism of action of this herbal remedy, in addition plots of these seeks are made for drug-target-disease networks. Conclusion: In this article, the role of microorganisms in causing of atherosclerosis and its treatment by a novel medicine such as licorice by using in silico approach. This effort should aid in the understanding of specific apparatuses for herbal drugs and the sighting of new drugs derived from plants.